2015
DOI: 10.1111/bjso.12137
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance as a function of disapproval and respect: The case of Muslims

Abstract: The article assesses a disapproval-respect model of tolerance according to which tolerance is made possible when disapproval of others' beliefs, preferences, or practices is balanced by respect for them as equal fellow citizens. Employing a sample of Muslims living in Germany, we predicted and found that such respect was more predictive of outgroup toleration when respondents disapproved rather than approved of the outgroups' beliefs, preferences, or practices. Moreover, respondents who displayed the critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(74 citation statements)
references
References 14 publications
6
67
0
1
Order By: Relevance
“…However, these processes, and politicization for that matter, need to be restrained by mutual recognition as different equals. It is encouraging that recent research on tolerance suggests that such recognition is indeed possible and able to play a pacifying role (Simon & Schaefer, , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these processes, and politicization for that matter, need to be restrained by mutual recognition as different equals. It is encouraging that recent research on tolerance suggests that such recognition is indeed possible and able to play a pacifying role (Simon & Schaefer, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The research reported in this article employed a longitudinal design to test two hypotheses concerning Muslims’ respect for and tolerance towards disapproved outgroups. In support of the outgroup respect–tolerance hypothesis derived from the disapproval–respect model of social tolerance (Simon, in press; Simon & Schaefer, ), our results strongly suggest that respect for disapproved outgroups is not just a correlate of tolerance towards those groups, but a causal antecedent. In support of the intergroup respect–reciprocity hypothesis, we identified respect from disapproved outgroups as an effective source of respect for disapproved outgroups and therefore ultimately as a (more distal) source of tolerance towards those groups.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the disapproval–respect model of social tolerance, we focused on Muslims’ tolerance towards disapproved outgroups and selected atheists, homosexuals, and feminists as target groups. Although Muslim respondents in Simon and Schaefer's () research had clearly expressed disapproval for each of these groups, the mean disapproval rating for feminists in our panel sample was only directionally, but not significantly below the neutral scale mid‐point ( p = .205; for atheists and homosexuals, p s < .001). While feminists may thus be a boundary case, it should be recalled that the hypothesized effect of Time 1 respect for a group on Time 2 tolerance towards that group was obtained for each of the three target groups (outgroup respect–tolerance hypothesis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations